Analysis of wire electrode wear ratio during WEDM of Al-metal matrix composite. (2022) - Kumar, Harmesh; Kumar, Rajesh; Manna, Alakesh; Kumar, Amresh
Abstract: The present work examines the effect of process parameters on wire electrode wear ratio (WWR) during wire-cut electric discharge machining WEDM of Al-metal matrix composites. The experimental investigation uses Box-Behnken's design of experiments. The experimental results have been used to develop WWR's prediction model. The efforts have been made to obtain the quality of machining through identifying the optimum machining conditions for minimizing WWR. Also, this work aims to investigate the variation of important response variables of WEDM processes, such as surface roughness (Ra ) and spark gap width, in relation to WWR. The test results revealed that the results of the developed prediction model of WWR are in good agreement with those obtained through practical experimentation. The study concludes that a high WWR value has been associated with a high spark gap width and a high surface roughness (Ra ).